Edukasi Pencegahan Injury Pada Kecelakaan Lalu Lintas di SMP Negeri 01 Gading Rejo - Muhammad Farhan Al Farisi; Mesya Mesya; Dwi Sulistiyawati (Abdinesia: Jurnal Pengabdian Kepada Masyarakat, 2024)
Provide objective of the In the implementation of education on Prevention of Injury in Traffic Accidents, there are several main problems that are a priority to be resolved, namely: Lack of Knowledge About Driving Safety, Lack of Understanding About Injury in Traffic Accidents, Lack of Knowledge for Traffic Accident Prevention, Lack of Continuous Education and Support Programs To overcome these problems, a comprehensive and sustainable education program is needed, including: Dissemination of science-based information through seminars, social media, and communities. Involvement of health workers in providing education and consultation services. Encourage understanding in preventing traffic accident injuries. With this approach, it is hoped that students can prevent traffic accident injuries, be more careful and always maintain safety when driving.